Deconstructing the climate migration myth: Assessing the impact of the 2022 floods on the movement of local populations in rural Punjab - Rabia Chaudhry; Eva Youkhana (University of Bonn, Center for Development Research (ZEF), 2024)
The link between climate change and migration has gained considerable recognition in recent years. Yet, it remains a complex and highly divisive issue in policy and academic circles alike. Fanned by populist politics and partisan media, misleading claims of large-scale migration of climate refugees from the Global South to the Global North continue to emerge.1 2 3 The argument is a simple one: as global temperatures continue to rise, the resultant extreme weather events such as floods, extreme temperatures, earthquakes, cyclones, land degradation, coastal erosion, rising sea levels, and droughts, etc. will be major drivers of mass migration from the Global South to the Global North (Christian Aid, 2007) (Adam, 2005). (...) Pakistan is one of the most vulnerable countries to climate change and climate-induced migration.7 While fears regarding its people being forced to flee for the Global North in response to the 2022 floods found its place in international policy circles, questions regarding how extreme and irregular climatic disasters impact the local populations' adaption and migration are yet to be asked. So far little research has been done to ascertain the nature and extent of migration linked to climate change in the context of Pakistan. This research aims to bridge that gap. Using the 2022 floods in Pakistan as an example we ask: what is the impact of extreme and irregular climatic disasters on outmigration of the local population? This is important and timely as domestic and international climate policy frameworks could benefit from localized evidence-based knowledge as opposed to falling back on 'climate reductive discourse' of migration and development interventions (Dewan, 2023).
Keywords: 330; Climate change; Flooding; Internal migration; Pakistan; Klimawandel; Überschwemmung; Binnenwanderung; Pakistan